Using SQ3R reading strategy to enhance reading comprehension among form 2 secondary school students of MARA Junior Science College, Sabah: a case of online instruction / Floriney Daniel - Daniel, Floriney (Akademi Pengajian Bahasa, 2021)
One of the crucial skills in reading is reading comprehension, writer’s messages written can reach others if they read what is written in the book or media electronic. But, reading without comprehend what is being read is another problem, especially for students. So, in order for students to extract and interpret the important message form the text, they must able to read and understand the text to receive the message or information conveyed by the writer. Students that learn English as their second or third language, will have difficulty to understand what they read without a closed monitor by their English teacher. Particularly for reading comprehension task. when all academic institutions closed due to the pandemic outburst on 18 March 2020, and Movement Control Order (MCO) introduced by the government to break the chain of Covid-19 infections, teachers have limited options, to continue the lessons. One of the available options among teachers is to conduct the lesson online. The internet technology that widely used in education nowadays helps most educators to deliver their lesson. So, in this study, the teacher will implement the SQ3R reading strategy to students using Microsoft Teams as a medium and will investigate the effectiveness of using Microsoft teams as a medium in teaching reading comprehension to Form 2 students online. This study will use a quantitative approach to compare students’ marks achievements before and after the implementation of SQ3R online. A total of 60 Form 2 students studying at MARA Junior Science College, Sabah will be involved in this study. Questionnaires and structures interview will be carried out to examine the students’ perception toward the integration of SQ3R using Microsoft Teams as a medium once they come back to school. Therefore, this study should be able to help other teachers with their online lessons and those want to improve their teaching method.